An Annulus-Sector Segmented Primary Mirror - X. X. Wei; X. J. Wan; B. Yang (IEEE Photonics Journal)
Ultrahigh resolution optical imaging with large aperture is increasingly desired in space-based remote sensing and imaging system, but it is usually limited by volume and mass constraints of launch vehicle due to size and weight of the imaging system. In this paper, an annulus-sector segment primary mirror is presented, which is in high obscuration with circularity symmetrical annulus-sector around. The different structure types of the annulus-sector segment aperture are discussed, while two important parameters, width–diameter ratio and the subaperture angle are also studied. An annulus-sector optical lens is processed to verify the image performance. Experimental results show that modulation transfer function of annulus-sector segment optical system can be up to 0.23(50 lp/mm), which approaches the optical resolution of full aperture optical system with smaller size and lighter weight.